Nonanalytic nonequilibrium field theory: Stochastic reheating of the Ising model - Camille Aron; Manas Kulkarni (Physical Review Research, 2020)
Many-body nonequilibrium steady states can be described by a Landau-Ginzburg theory if one allows nonanalytic terms in the potential. We substantiate this claim by working out the case of the Ising magnet in contact with a thermal bath and undergoing stochastic reheating: It is reset to a paramagnet at random times. By a combination of stochastic field theory and Monte Carlo simulations, we unveil how the usual φ^{4} potential is deformed by nonanalytic operators of intrinsic nonequilibrium nature. We demonstrate their infrared relevance at low temperatures by a renormalization-group analysis of the nonequilibrium steady state. The equilibrium ferromagnetic fixed point is thus destabilized by stochastic reheating and we identify the new nonequilibrium fixed point.